Anosmia due to bilateral papillary atrophy : a case report: Poster Presentation - Case Report - Resident - Anggia Dwi Kora; Dr. dr. M. Hidayat Sp.M(K) (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Papillary atrophy refers to degeneration of the optic nerve, which occurs as an end result of a pathological process that damages the axons, with ophthalmoscopic observation showing pallor of the optic nerve papillae which generally accompanies permanent damage to the optic nerve. Case Illustration : It was reported that a 36 year old woman came to the polyclinic with complaints of not being able to see in both eyes since 8 months ago. Complaints of blurred vision in both eyes are followed by smell that cannot smell. This complaint has been getting worse for the past 2 weeks. On brain MRI examination, results were obtained with SOL impressions in the midline frontalis area with perifocal edema ec, suspected olfactory groove meningioma. Discussion : In this case SOL is located in the midline frontal area so that the patient complains of loss of smell sensation (anosmia). The presence of a frontal or subfrontal tumor can compress the optic tract and optic nerve together. Optic tract compression will cause anosmia. Olfactory disturbances are strongly associated with anterior cerebral fossa tumors. Conclusion : Secondary papillary atrophy is caused by increased intracranial pressure caused by a mass tumor which is preceded by papilledema signs and eventually becomes papillary atrophy, and gives a pale optic papillae with blurred boundaries. Brain CT scan examinations are important to estimate the location of the lesion.